Accuracy of prediction of maximum resistance at increased holding times based on a three seconds maximum static strength test of the three main strength elements on rings - Schärer, C.; Hübner, K. (Science of Gymnastics Journal, 2016)
On rings in men`s artistic gymnastics, a high degree of relative maximum strength is crucial to present up to seven strength elements in the required quality in the routine. To increase this specific strength and strength endurance the coaches often prolong the holding times of those elements by using the devices counterweight and additional weight in training. The purpose of this study was to investigate the predictability of the maximum resistance (MR) (minimal counterweight/maximum additional weight) at five and seven seconds holding times based on the MR at three seconds of the elements Iron Cross (C), Support Scale (SS) and Swallow (S) and to provide coaches with a reliable conversion table that predicts the individual training weights at different holding times. Ten male gymnasts of the Swiss National Team performed a specific static MR-Test (three, five and seven seconds holding time) of the elements C, SS and S. The results showed a significant decrease in MR as holding time increased (t-Test: p < 0.001). The standard error of estimate (SEE) and explained variance (R2) revealed that the prediction of MR at five seconds (SEE 0.52 kg to 1.03 kg, R2 0.92 to 1.00) was more accurate than at seven seconds holding time (SEE 0.95 kg to 2.08 kg, R2 0.88 to 0.98). Based on the linear regression equations, a useful conversion table was established that predicts the MR at five and seven seconds holding time based on the three seconds MR at each of the tested elements. Keywords: artistic gymnastics, rings, strength, swallow, cross, support scale.